Measures of the British Force in Iraq and their managements to limitate the pread of Malaria among its troops (Documentary Study) (Journal of the College of Education for Women, 2019)
Historical scripts and Academic studies have bestrewed almost all the events of the movement of march 1941 . Yet the need was present to shine more light on important sides . These important sides were neglected due to some reasons among which came the absence of the historical material which can make a new historical detection. Then there were historical topics concerning our research which comes within context of sanitarily conditions , rarely seizes the attention of the researchers for many reasons some of them were not subjective.The spread of Malaria among the British force was one of the sanitarily conditions that were related to the movement of march since their arrival to Basra city and its continuous spread after the second invasion for Iraq after the failure of the movement of March 1941 . It endangered the existence of British troops and that led them to strengthen their faculty in manipulating Malaria and its treatment .in spite of all that, the factual situation imposes the admission of not belittling the efforts exerted by the British troops to contain this sanitary problem among its troops . And never to overlook the spread of the medical units which were provided with all the equipment of Malaria treatment and specialized medical staffes who were delegated to Iraq that witnessed quantative as well as qualitive improvement. It is important to take into consideration that the British troops spread in a country that is invaded by Malaria and never save any city or village .